Theoretical Evaluation of Michelia Species’ Bioactive Compounds and Theraupetic Potential: A Literature Review - Nurul Oktaviana; Nadia Isnaini; Essy Harnelly; Zulkarnain Zulkarnain; Syaifullah Muhammad; Misrahanum Misrahanum (Graha Primera Saintifika, 2023)
Michelia alba is a multifunctional plant found in Indonesia and is also called magnolia. Michelia alba is a tree known for its essential oil, which has long been used as a fragrance ingredient in perfumes and cosmetics. The potential of M. alba is immense for use in the prevention and treatment of disease as well as the management of human health and wellness. To date, there have been few publications regarding the biological activities of M. alba, focusing on tyrosinase inhibitory, antibacterial, antidiabetic, anti-inflammatory and antioxidant activities. However, M. alba may have additional undiscovered biological activities associated with its bioactive compounds. The purpose of this literature review research is to find out the bioactive compounds and therapeutic potential of the M. alba plant through literature searches that can be a reference for further research. The literature review method is carried out by searching and collecting data from literature sources obtained from several national and international journals that review bioactive compounds and the therapeutic potential of M. alba plants. Based on the literature review, it was found that M. alba has bioactive compounds namely linalool (72.8 flower oil and 80.1% leaf oil), α-terpineol (6.04% flower oil), phenylethyl alcohol (2.58% flower oil), β-pinene (2.39% flower oil) and geraniol (1, 23%) which have therapeutic activities such as mental health disorders, anticancer, anti-inflammatory, antihypertensive, antidiabetic, antihyperlipidemia, antimaagic, antidiarrheal, anti-asthma, and antihyperpigmentation. In traditional medicine it is used to treat fever, syphilis, gonorrhea and malaria, bronchitis, prostatitis, cancer, headache, sinusitis, cough, inflammation of the respiratory tract, chest fullness, flatulence, nausea, body and underarm odor, and vaginal discharge.